Studi Etnobotani Tumbuhan yang Digunakan dalam Upacara Kematian Saur Matua - Enjely Putri Marpaung; M. Idris (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the types, parts and essential values of the plants used in the Saur Matua death ceremony. The method used is quantitative-qualitative. The results showed that there were six plant species from 4 families, namely Poaceae, Moraceae, Liliaceae and Laxmanniaceae. The dominant plant parts used are leaves and stems. The highest plant importance values were rice (ICS = 50), ompu-ompu (ICS = 12) and banyan trees (ICS = 2). In conclusion, the types of plants used in the Saur Matua death ceremony are banyan trees, Ompu-ompu, rice, ground fan orchids, sanggar or pimping and Silinjung with leaves and stems as the dominant plant parts used and rice is a type that has essential value tallest plant. Keywords: Index of Cultural Significance, Liliaceae, Nibung Hangus, Poaceae, Saur Matua